The emergence of arboviruses changes the profile of viral meningitis in Salvador, Bahia: A case series - Dias, Tamiris T.; Tauro, Laura B.; Macêdo, Lara E. N.; Brito, Liz O.; Ribeiro, Victor H. O.; Santos, Cleiton S.; Jacob-Nascimento, Leile C.; Vilas-Boas, Letícia S.; Amado, Caio; Barbosa, Paula S.; Reis, Joice N.; Campos, Gubio Soares; et al. (Frontiers in Tropical Diseases, 2022)
Recently, different arboviruses became endemic in Brazil mostly causing acute febrile illnesses, however, neurological manifestations have also been reported. This study aimed to investigate which viruses were involved in the meningitis etiology and the contribution of the circulating arboviruses. From June 2014 to February 2016, 170 patients with suspected viral meningitis were identified in Couto Maia Hospital, Salvador-BA, Brazil. Their CSF samples were investigated by nucleic acid tests for possible viral etiology: DENV1-4, ZIKV, EV, and the HHV1-5 complex. Also, ELISA was carried out in a subgroup of remaining samples for detection of DENV IgM and NS1 antigen, CHIKV IgM and ZIKV IgM. Thirty-seven patients were PCR or ELISA positive for at least one of the studied viruses (overall positivity 21.8%). EV was the agent most frequently detected (10 cases; 27.0%), along with DENV1-4 (10 cases; 27.0%); followed by CHIKV (6 cases; 16.2%), ZIKV (6 cases; 16.2%), and HHV-3 (VZV) (1 case; 2.7%). Four cases (10.8%) presented viral co-infection detected: DENV1 + CHIKV, DENV1 + EV, DENV4 + ZIKV, and CHIKV + ZIKV. Arboviruses (DENV, CHIKV and ZIKV) accounted for the great majority of cases (26 cases; 70.3%) of all single and co-infections: DENV has been the most frequently detected arbovirus (13 cases; 35.1%). Among non-arboviral meningitis, the most common etiology was the EV (11 cases; 29.7%). Arboviruses accounted for the majority of identified viruses among patients with suspected viral meningitis. In areas where arboviruses are endemic it is crucial to consider them in the differential diagnosis of meningitis.